A little good is good enough: Ethical consumption, cheap excuses, and moral self-licensing - Jannis Engel; Nora Szech (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
We explore the role of cheap excuses in product choice. If a product improves upon one ethically relevant dimension, agents may care less about other, completely independent ethical facets of the product. This 'static moral self-licensing' would extend the logic of the well-studied moral self-licensing over time. Our data document that static moral self-licensing exists. Furthermore, effects spill over to later, unrelated but ethically relevant contexts. Thus, static moral self-licensing and moral self-licensing over time amplify each other. Outsiders, though incentivized for correct estimates, are completely oblivious to effects of moral selflicensing, both, static and over time.
Keywords: D03; D84; 330; moral self-licensing; moral spillovers; cheap excuses; outsider beliefs; moral personality; homo moralis; preference module